32.8k views
5 votes
Solve for t.

-5 − 2t = 3t

User Nebelhom
by
6.0k points

2 Answers

4 votes

First, we have to isolate the t, or keep it by itself, to solve. To do that, we need to move everything with t in it to on side.

-5 - 2t + 2t = 3t + 2t

The -2t and + 2t cross out, leaving us with t on one side, which is exactly what we want!

-5 = 5t

But t isn't alone yet. We need to get rid of its five. To do that, we need to use the same process: use the opposite symbol. In 5t, 5 is being multiplied by t. To get rid of, we need to divide 5. BUT the mega rule in algebra... what you do to one side you must do to the other, or else the equation would not be true anymore, so...

-5/5 = 5t/5

-1 = t

There's your answer! Hope this helps!

User Vincent Guyader
by
5.6k points
2 votes
t is equal to -1.
  1. Add 2t to both sides of the equation. -5 = 5t
  2. Divide both sides of the equation by -5. 1 = -t
  3. Multiply both sides of the equation by -1. -1 = t
User Nkhil
by
5.6k points